Nitrogen Mineralization of a Loam Soil Supplemented with Organic–Inorganic Amendments under Laboratory Incubation - Abbasi, M. Kaleem; Khaliq, Abdul (Frontiers in Plant Science, 2016)
The quantification of nitrogen (N) supplying capacity of organic amendments applied to a soil is of immense importance to examine synchronization, N release capacity, and fertilizer values of these added materials. The aims of the present study was to determine the potential N mineralization and subsequent nitrification of separate and combined use of poultry manure (PM), wheat straw residues (WSR), and urea N (UN) applied to a loam soil incubated periodically over 140 days period. In addition, changes in total soil N and carbon contents were also monitored during the study. Treatments included: PM100, WSR100, PM50 + WSR50, UN100, UN50 + PM50, UN50 + WSR50, UN50 + PM25 + WSR25, and a control (unfertilized). All the amendments were applied on an N-equivalent basis at the rate of 200 mg N kg-1. Results indicated that a substantial quantity of N had been released from the added amendments into the soil mineral pool and the net cumulative N mineralized varied between 39 and 147 mg N kg-1, lowest in the WSR and highest in the UN50 + PM50. Significant differences were observed among the amendments and the net mineral N derived from a separate and combined use of PM was greater than the other treatments. The net cumulative N nitrified (NCNN) varied between 16 and 126 mg kg-1, highest in UN50 + PM50 treatment. On average, percentage conversion of added N into available N by different amendments varied between 21 and 80%, while conversion of applied N into NO3-–N ranged between 9 and 65%, and the treatment UN50 + PM50 displayed the highest N recovery. Urea N when applied alone showed disappearance of 37% N (N unaccounted for) at the end while application of PM and WSR with UN reduced N disappearance and increased N retention in the mineral pool for a longer period. Organic amendments alone or in combination with UN improved organic matter buildup and increased soil N concentration. These results demonstrate the existence of substantial amounts of N reserves present in PM and WSR that can be utilized efficiently and effectively as potential N source for the management of nutrient poor soils and plant growth.